A Mobile App (Smart Dental Alarm) on Improving Tooth Brushing Skills among Early Childhood - Dewi Ratna; Djamil Masrifan; Wiyatini Tri; Supriyana Supriyana; Sunarjo Lanny (Alta Dharma Publisher, 2021)
ABSTRACT Background: Dental caries in children aged 5-9 reach 90.1%. This situation is due to the poor tooth brushing behavior of children. Smart Dental Alarm is a modification of Android-based early childhood dental hygiene education media which is equipped with various features to increase tooth brushing skills Objective: The aim of the research was to produce a “Smart Dental Alarm” application as a media for dental hygiene education to increase the skill of tooth brushing in early childhood. Methods: The research was undertaken with Research and Devoloment (R&D) method, while the model assesment used Quasy-Experimental Randomized Control Group of Pretest and Posttest Design. The number of research subjects was 33 children in each group, comprises group 1 as Intervention group with Smart Dental Alarmand group 2 as Control group with Power Point. Data were tested using ISO 9126, Shapiro Wilk, Freidman, and Man Whitney. Result: The results of this study indicate that Smart Dental Alarm is more effective in increasing the knowledge and behavior of the tooth brushing behavior in preschool children than using power point regarding the pre-test, post-test 1 and 2 which obtain p-Value in 0.000. Conclusion: Smart Dental Alarm is more effective in increasing tooth brushing skill and reducing caries in early age children than power points. Key Words: Early age children, Smart Dental Alarm,Tooth brushing skill